Cardiomiopatia dilatada após apresentação inicial de insuficiência cardíaca descompensada em crianças e adolescentes: proposta terapêutica, fatores prognósticos e estratificação de risco - Fatima Derlene da Rocha Araujo (2016)
Introduction: dilated cardiomyopathy (DCM) is the most common cause of cardiomyopathy in children and its primary manifestation is heart failure (HF). Children with an initial picture of decompensated HF are at higher risk of dying or undergoing a heart transplant. The scores to evaluate the probability of an unfavorable progression allow early referral to specialized centers. Objectives: to assess the clinical factors and diagnostic tests associated to the outcome (death or heart transplant), in children and adolescents with initial presentation of DCM due to decompensated HF, and to develop a risk stratification score. Methods: an observational, longitudinal study including patients under treatment since 1999, and, prospectively, those admitted from January 2010 to December 2015. Patients aged from zero to 18 years were enrolled after discharge from the intensive care unit with diagnoses of DCM and HF functional class III or IV (New York Heart Association - NYHA). Excluded were patients with congenital heart diseases, pulmonary hypertension or myocardial dysfunction caused by sepsis, primary arrhythmias, neuromyopathy, valve diseases or ischemia. Six months after complete treatment, a new assessment - clinical, laboratory and Doppler echocardiography - was performed and related to the outcome. The probability of the outcome was estimated according to the proposed scoring system. Statistical analysis: the Statistical Package for Social Sciences (SPSS) version 14.0 was used and the results were expressed in numbers and proportion, or measures of central tendency and dispersion. The Mann-Whitney, and chi-squared or Fisher´s tests were utilized to compare the differences of the continuous and categorical variables, respectively. The receiver operating characteristic (ROC) curve was used to assess sensitivity and specificity of statistically significant variables, and the Kaplan-Meier curve, for analysis of event-free survival. A p-value of 0.05 was set for null hypothesis rejection. Results: Fifty-seven patients, followed up for 6 months to 18.3 years, and mean age upon diagnosis of 48 months, were enrolled. The cause of DCM was identified in 79% of patients. Thirty patients (52.6%) had clinical improvement and 16 (28.1%) were transplanted or died. The 1-, 5- and 10-year event-free survival rates were 94.7%, 76.2%, 54.0%, respectively. There were no differences in survival regarding etiology, sex or age. In the multivariate analysis, the independent prognostic factors were body mass index, Ross heart failure classification and increased bilirubin levels. The score developed was related to risk stratification, and a high risk was 15 (area under the curve of 94%, p<0.001, 95% confidence interval: 0.89-0.99). The survival curves for risk stratification scores were different as to outcome (p<0.0001). Conclusion: patients at high risk should receive optimized therapy quickly, and if response to treatment fails, they must be referred to transplant assessment.